Determination of Seismicity with Grid Searching Method (Case Study of Gempabumi Pulung, Ponorogo Regency February 2011) - Petrus Demon Sili; Adi Susilo; Sukir Maryanto (Natural B, Journal of Health and Environmental Sciences, 2013)
Pulung Region, Ponorogo major city, Indonesia is one of the area in Indonesia which is prone of the local earthquake threat. Since 1963, there was about 7 big earthquakes, where 1 earthquake was destroyed earthquake and 2 events occured at the Pulung region. The two those earthquakes occured at Pulung were in 1993 and 1999, with the magnitude was 3.7 SR  and 5.6 SR respectively. The last event was on February 2011, therefore it’s necessary to study and determine the  seismicity. In addition the relocation analysis using Grid Searching seismicity showed that the distribution of earthquakes shifted to the East direction, with the coordinat of from  7.8122º to 7153º SL and 111.6360o to 111.7303° EL, the depth of earthquakes varies between 0.532 km and 7250 km, and the magnitude was between 1.4 and 2.0 SR. It is hoped that this result can be used for the govermnment of Ponorogo to mitigate of earthquake impact.